2020
DOI: 10.1002/elsc.202000021
|View full text |Cite
|
Sign up to set email alerts
|

Microflow system promotes acetaminophen crystal nucleation

Abstract: It is known that interfaces have various impacts on crystallization from a solution. Here, we describe crystallization of acetaminophen using a microflow channel, in which two liquids meet and form a liquid–liquid interface due to laminar flow, resulting in uniform mixing of solvents on the molecular scale. In the anti‐solvent method, the microflow mixing promoted the crystallization more than bulk mixing. Furthermore, increased flow rate encouraged crystal formation, and a metastable form appeared under a cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Form I is used in commercial formulations. To date, it has been shown that acetaminophen crystal nucleation is promoted by a microflow system [25]. Furthermore, crystallization of the unstable phases by femtosecond laser and ultrasound irradiations has been reported [11,12,26].…”
Section: Introductionmentioning
confidence: 99%
“…Form I is used in commercial formulations. To date, it has been shown that acetaminophen crystal nucleation is promoted by a microflow system [25]. Furthermore, crystallization of the unstable phases by femtosecond laser and ultrasound irradiations has been reported [11,12,26].…”
Section: Introductionmentioning
confidence: 99%